Comparative analysis of Kazakhstani and South Korean television channels - Koksegenova, А.Н. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2022)
Abstract. Television entertainment programs play an important role in the formation of the media and the development of national values of a new generation. The article considers the current state of Kazakhstani and South Korean entertainment programs and broadcasting channels. Problems have been identified, trends and prospects for the development of Kazakhstani and South Korean entertainment programs have been defined. Comparative analysis of the programs are conducted, and based on the criteria presented by the author.